PEMANFAATAN MEDIA PEMBELAJARAN DAPAT MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IX. 2 SMP NEGERI 1 SOE - SARAH YANSE SAE (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
The use of appropriate media will also determine the level of success of the learning process as well as in the learning process both in explaining the subject matter, instilling experience and efforts to help students to remember the learning experiences that have been obtained longer. The use of media in the learning process should vary and remain in accordance with the material being taught so that the teaching and learning process can be carried out properly. Media as a tool in the learning process is a fact that cannot be denied because the existence of media can help the teacher's task in conveying messages from the lesson material given by the teacher to students. Besides that, it can also represent what the teacher is unable to say through certain words or sentences. Educational media are facilities and infrastructure to support the implementation of learning activities. For this reason, all parties involved in the learning process need to pay adequate attention to this problem. The existence of media cannot be simply ignored in the learning process, this is because without educational media, the implementation of learning cannot run properly, including in the learning process in the field of study. Learning media is a tool to assist teachers in providing quick understanding to students, in other words that media is a tool that can help teachers explain the purpose of the learning discussion conveyed. The use of media in class is very helpful in the process of explaining learning material and can also help students in more concrete and focused explanations. ABSTRAKPenggunaan media yang tepat akan turut menentukan tingkat keberhasilan proses pembelajaran begitu juga halnya dalam proses pembelajaran baik dalam menjelaskan materi pelajaran, penanaman pengalaman serta upaya membantu siswa untuk mengingat lebih lama pengalaman belajar yang telah diperoleh. Penggunaan media dalam proses pembelajaran hendaknya bervariasi dan tetap sesuai dengan materi yang diajarkan agar proses belajar mengajar dapat terlaksana dengan sebaiknya. Media sebagai alat bantu dalam proses pembelajaran adalah suatu kenyataan yang tidak dapat dipungkiri karena dengan adanya media dapat membantu tugas guru dalam menyampaikan pesan-pesan dari bahan pelajaran yang diberikan oleh guru kepada anak didik. Selain itu juga dapat mewakili apa apa yang kurang mampu guru ucapkan melalui kata-kata atau kalimat tertentu. Media pendidikan merupakan sarana dan prasarana untuk menunjang terlaksananya kegiatan pembelajaran. Untuk itu semua pihak yang terlibat dalam proses pembelajaran perlu memberikan perhatian yang memadai untuk masalah ini. Keberadaan media tidak dapat diabaikan begitu saja dalam proses pembelajaran hal ini dikarenakan tanpa adanya media pendidikan, pelaksanaan pembelajaran tidak dapat berjalan dengan baik termasuk dalam proses pembelajaran bidang studi. Media pembelajaran meruapakan sebuah alat untuk membantu guru dalam memberikan pemahaman cepat kepada siswa, dengan kata lain bahwa media adalah alat bantu yang dapat membatu guru untuk menjelaskan maksud dari pembahasan pembelajaran yang disampaikan. Penggunaan media di kelas sangat membantu dalam proses menjelaskan materi pembelajaran dan juga dapat membantu siswa dalam penjelasan yang lebih konkrit dan terarah.